We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
110
5
avatar+2448 

plz help

 Nov 27, 2018
 #1
avatar+18018 
+3

I'll show you how to do the FIRST one....you shoyld be able to do the others....

 

(y-y1) = m(x-x1)

(y-4) = 3(x-(-1))

y-4 = 3x +3

y=3x+7      ta - da !       Go RP....try the others....cheeky

 Nov 27, 2018
 #2
avatar+2448 
+1

2) y-y1=m(x-x1)

y-1=1/2(x-6)

y-1=1/2x-3

y=1/2x-2

Am I right?

RainbowPanda  Nov 27, 2018
edited by RainbowPanda  Nov 27, 2018
 #4
avatar+18018 
+2

Correct-o-mundo !

ElectricPavlov  Nov 27, 2018
 #3
avatar+99523 
+2

Thanks, EP !!!

 

Here's another way

 

(1)   m = 3            point = ( - 1, 4)

 

Write the equation as

 

y = slope ( x -   the x coordinate)   + the y coordinate     

 

So we have

 

y = 3 ( x -  -1) + 4

 

y  = 3 ( x + 1) + 4       simplify

 

y = 3x + 3 + 4

 

y = 3x + 7

 

 

cool cool cool

 Nov 27, 2018
 #5
avatar+99523 
+1

Here's (2)  using my method

 

m = (1/2)        point = ( 6, 1)

 

y = slope ( x -   x coordinate ) + y coordinate

 

y = (1/2) ( x - 6) + 1    simplfy

 

y = (1/2)x - 6/2 + 1

 

y = (1/2)x - 3 + 1

 

y = (1/2) x - 2 

 

So....Correct !!!

 

 

cool cool cool

 Nov 27, 2018

5 Online Users